Health Risk Behaviours by Immigrants' Duration of Residence: A Systematic Review and Meta-Analysis - Sol P. Juárez; Sol P. Juárez; Helena Honkaniemi; Helena Honkaniemi; Nina-Katri Gustafsson; Nina-Katri Gustafsson; Mikael Rostila; Mikael Rostila; Lisa Berg; Lisa Berg (Frontiers Media S.A., 2022)
Objectives: The aim was to systematically review and synthesise international evidence on changes in health risk behaviours by immigrants' duration of residence.Methods: We searched literature databases for peer-reviewed quantitative studies published from 2000 to 2019, examining alcohol, drug and tobacco use; physical inactivity; and dietary habits by duration of residence.Results: Narrative synthesis indicated that immigrants tend to adopt health risk behaviours with longer residence in North America, with larger variation in effect sizes and directionality in other contexts. Random-effects meta-analyses examining the pooled effect across all receiving countries and immigrant groups showed lower odds of smoking (OR 0.54, 0.46-0.63, I2 = 68.7%) and alcohol use (OR 0.61, 0.47-0.75, I2 = 93.5%) and higher odds of physical inactivity (OR 1.71, 1.40-2.02, I2 = 99.1%) among immigrants than natives, but did not provide support for a universal trend by duration of residence.Conclusion: Findings suggest that duration of residence could serve as an effective instrument to monitor immigrants' health changes. However, differences in receiving country contexts and immigrant populations' composition seem to be important to predict the level and direction of behavioural change.Systematic Review Registration:https://www.crd.york.ac.uk/prospero/, PROSPERO CRD42018108881.